Spiritual Efforts in Coping With Disasters in The Berat Sengkala Ritual: A Perspective By Roland Barthes - Rizqy Rafikasari; Sucipto Hadi Purnomo; Rahma Ari Widiastuti (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2026)
The Berat Sengkala tradition is a customary ritual practiced by the community of Lamuk Village, Kaliwiro District, Wonosobo Regency, Central Java, as a form of spiritual endeavor in response to calamities, particularly natural disasters, crop failures, and agricultural pest infestations. This ritual contains a system of symbols that represents the relationship between humans, nature, God, and ancestors; however, its symbolic meanings have not been extensively examined. This study aims to reveal the symbolic meanings embedded in the ritual while also understanding the community's form of spiritual endeavor in confronting calamities through the semiotic perspective of Roland Barthes. This research employed a qualitative approach using an ethnographic method. Data were collected through participant observation, in-depth interviews with community elders and local residents, and documentation of the ritual process, which were then analyzed using Roland Barthes' concepts of denotation, connotation, and myth. The findings indicate that holy water, agricultural produce offerings, and collective prayers form a system of signs representing life, divine protection, ecological awareness, gratitude, social solidarity, and respect for ancestors. At the level of myth, the ritual reinforces the collective belief that maintaining a harmonious relationship among humans, nature, God, and ancestors constitutes a form of spiritual endeavor in dealing with calamities and ensuring the continuity of community life. These calamities include natural disasters such as landslides, crop failures, and attacks by plant pests, including insects, rats, and birds, which can reduce agricultural productivity and ultimately lead to harvest failure, while simultaneously preserving the sustainability of community life.